Wanita Dalam Falsafah Jawa : (Analisis Kekerasan Simbolik Terhadap Wanita) - Arum Kholifatul Alyyah -; Kiki Luluk Khondziroh (Universitas Halu Oleo (UHO), 2024)
This article analyzes injustice against women in Javanese philosophy with the theory of symbolic violence used as a point of view to reveal how gender inequality occurs in the form of violence against women who are required to submit and obey their husbands and parents. Using qualitative methods with an ethnographic approach, the researcher wants to present how Javanese women's views on life have been passed down from generation to generation regarding the position of women as a result of Javanese philosophy. The results of the research show that Javanese women should not dispute orders from their parents or husband. This research concludes that the gender inequality that occurs between men and women in Javanese philosophy limits women in expressing their opinions, especially in public spaces where the gender domination experienced by women is one of the underlying causes of symbolic violence.